Capital and Skills Development of Women Migrant Workers: A Case of Women Migrant Worker from Myanmar, Lao People’s Democratic Republic, and Cambodia in Thailand - Wichaiya, Watinee; Tarat, Saranya (Thammasat Journal, 2022)
The objectives of this article were to study skills development situation in Thailand and to explore the relationship between women migrant workers’ skills and their employment. The Pierre Bourdieu's concept of capital was used as a theoretical framework. This qualitative research depended on an in-depth interview method as a data collection tool. The key informants were 16 women migrant workers from three nationalities (Myanmar, Lao People’s Democratic Republic, and Cambodia) in four sectors (construction, manufacturing, hospitality, and domestic work sectors) and in four provinces (Bangkok, Samut Sakhon, Chonburi, and Chiang Mai). Other key informants were six civil society officers who work with women migrant workers. The study of skills development situation has revealed that a small number of women migrant workers have gained skills from their countries of origin and were concentrated in some sectors. The nationality, gender and free time of women migrant workers were conditions that resulted in their skills development. Women migrant workers’ skills and skills certification were important cultural capital for their employment in Thailand. In such cases, skill development and certification can transform their cultural capital into economic capital as well as symbolic capital. In so doing, their increased skills have made them get increased income and recognizable from their colleagues and employers. Skills have thus distinguished the classes and class fractions of women migrant workers in Thailand.